Globalizing Higher Education and its Impact on Indian Expat Students (A Case Study of Indian Expat Students Living in UAE) - Ansari Ebrahim (International Journal of Engineering and Management Research, 2021)
Education is the backbone of a progressive society as it is clear from the statement of Thomas Jefferson “educate the masses” as he believed that in order to make changes in a society, the whole masses should be educated. The term ‘education’ is a popular and common term used by everybody but understood by very few in its right perspective. In educational text books it is defined as a purposive, conscious or unconscious, psychological, sociological, scientific and philosophical process that brings about development of the individual to fullest extent and also the maximum development of society in such a way that both enjoy happiness and prosperity. Despite the existence of infrastructural facilities, economic status and availability of various educational courses, the attitude towards higher education and learning is not found to be positive among the Indian expat students. The ultimate objective of this study is to find out the factors that influence the attitude of the students towards higher education and recommend sufficient measures to improve it.